Communities as 'renewable energy' for healthcare services? a multimethods study into the form, scale and role of voluntary support for community hospitals in England. Issue 10 (7th October 2019) - Ellis Paine, Angela; Kamerāde, Daiga; Mohan, John; Davidson, Deborah
Abstract : Objective: To examine the forms, scale and role of community and voluntary support for community hospitals in England. Design: A multimethods study. Quantitative analysis of Charity Commission data on levels of volunteering and voluntary income for charities supporting community hospitals. Nine qualitative case studies of community hospitals and their surrounding communities, including interviews and focus groups. Setting: Community hospitals in England and their surrounding communities. Participants: Charity Commission data for 245 community hospital Leagues of Friends. Interviews with staff (89), patients (60), carers (28), volunteers (35), community representatives (20), managers and commissioners (9). Focus groups with multidisciplinary teams (8 groups across nine sites, involving 43 respondents), volunteers (6 groups, 33 respondents) and community stakeholders (8 groups, 54 respondents). Results: Communities support community hospitals through: human resources (average=24 volunteers a year per hospital); financial resources (median voluntary income = £15 632); practical resources through services and activities provided by voluntary and community groups; and intellectual resources (eg, consultation and coproduction). Communities provide valuable supplementary resources to the National Health Service, enhancing community hospital services, patient experience, staff morale and volunteer well-being. Such resources, however, vary in level and form from hospital to hospital and over time: voluntary income is on the decline, as is membership of League of Friends, and it can be hard to recruit regular, active volunteers. Conclusions: Communities can be a significant resource for healthcare services, in ways which can enhance patient experience and service quality. Harnessing that resource, however, is not straight forward and there is a perception that it might be becoming more difficult questioning the extent to which it can be considered sustainable or 'renewable'.